Doing the Great British Class Survey. Issue 2 (May 2015) - Devine, Fiona; Snee, Helene
Abstract This paper introduces the Great British Class Survey and describes how it came to be, providing an insight into the work that has led to this special issue on the contemporary British elite. We discuss initial work with the BBC Lab UK team, the construction of the web survey and its launch. We also consider the response rate and how an additional face‐to‐face nationally representative survey was then commissioned to deal with sample skew. The way in which subsequent analysis addresses this challenge is also addressed, along with how this 'problem' has provided rich, granular data on the most privileged and powerful in UK society. We reflect on a piece of research which enjoyed considerable attention, and how we might interpret this in terms of public engagement. We also acknowledge some of the immediate academic responses to this innovative collaborative adventure. Finally, we indicate how the GBCS team will be developing this work in the future, before outlining how the papers in this special issue offer insights into the anatomy of power and privilege in modern Britain.